THEORY OF MANAGER DECISION MAKING: USE OF CIVIL SERVANTS IN MODERN MANAGEMENT PRACTICE - Vynogradova , N.; Serogina, N. (Theory and Practice of Public Administration, 2020)
The article deals with the analysis of the modern managerial practice of civil servants in terms of using the theory of managerial decisions in their activities. When making manager decisions, this analysis is complicated by the lack of available information about the application of the economic and mathematical apparatus, heuristic methods, correlation analysis, game theory, expert assessments, simulation, etc. Possible technologies of managerial decisions are investigated in the context of two main models: rational and psychological (behavioral). It is noted that the current practice of public managerial decisions is based on situational analysis. When making decisions, a civil servant mostly uses simple heuristic rules and does not use a complex algorithmic process. The risks that may arise during goal setting are identified. In particular, they are connected with the multiplicity of goals and incorrect definition of priorities, political expediency, and concealment of the real goals of managerial decisions. It is concluded that the detachment of the managerial decisions theory and the practice of forming managerial impacts must be overcome. The use of scientifically based management, methodology of policy analysis, systems analysis, and strategic management is important to making managerial decisions. It is determined that the prerequisite for successful managerial decisions is the professionalization of civil servants with their training; ensuring compliance of decisions taken with basic social values, moral norms and principles. Openness and transparency of the management decision-making process and involvement of civil society institutions in their production will contribute to the improvement of managerial decisions.